Senecio guatulamensis, nueva especie de Asteraceae endémica de Chile - Muñoz-Schick, Mélica; Moreira-Muñoz, Andrés; de Trenqualye, Alain (Gayana Botánica, 2016)
A new species of Senecio is described, on the basis of recent prospections in the Andes of Limarí valley, Coquimbo Region. The new species pertains to the Senecio section, series Andina. Differences with allied taxa are discussed.